2017
DOI: 10.1177/1010428317699114
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides accumulation and breast cancer: A hospital-based case–control study

Abstract: The aim of this study is to detect the accumulation status of organochlorine pesticides in breast cancer patients and to explore the relationship between organochlorine pesticides contamination and breast cancer development. We conducted a hospital-based case-control study in 56 patients with breast cancer and 46 patients with benign breast disease. We detected the accumulation level of several organochlorine pesticides products (β-hexachlorocyclohexane, γ-hexachlorocyclohexane, polychlorinated biphenyls-28, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
16
1
3
Order By: Relevance
“…Although recent case-control studies suggested positive associations between breast cancer and PCBs [ 33 35 ], we found no increase in breast or uterine cancer mortality. Our results accord with findings from previous Yusho and Yucheng cohort studies [ 11 , 12 , 16 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Although recent case-control studies suggested positive associations between breast cancer and PCBs [ 33 35 ], we found no increase in breast or uterine cancer mortality. Our results accord with findings from previous Yusho and Yucheng cohort studies [ 11 , 12 , 16 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding pesticides in particular, several studies have suggested their potential genotoxicity, immunotoxicity, ability to act as tumor promoters and as endocrine disruptors, as the pathophysiology mechanisms related to the increasing risk of breast cancer [9,10,11,12,13,14]. In humans, a case-control study including 1169 cases and 1743 controls was conducted in Canada from 2009 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…50 Qingdao, China, offered evidence that PCB 28 and 52 (both of which belong to group IA) are associated with an increased risk for breast cancer. 60,61 The heavy consumption of fish is likely responsible for the strong correlation between breast cancer risk and the less persistent congener found in native populations, although this is not mentioned in either study. In view of this matter, we suggest that not too much attention be paid to the effects of lower chlorinated congeners, because the human exposure level is very low, and although lower chlorinated congeners have stronger estrogenic activity than higher chlorinated ones, their half-lives are much shorter, so it is hard to produce the necessary chronic exposure.…”
Section: Highlights On Results Of Subgroup Analysis Pcb Structure-spementioning
confidence: 90%